A whole-molecule immunocapture LC–MS approach for the in vivo quantitation of biotherapeutics. (October 2016) - Kellie, John F; Kehler, Jonathan R; Mencken, Thomas J; Snell, Richard J; Hottenstein, Charles S
Aim: Large-molecule biotherapeutic quantitation in vivo by LC–MS has traditionally relied on enzymatic digestion followed by quantitation of a 'surrogate peptide' to infer whole-molecule concentration. MS methods presented here measure the whole molecule and provide a platform to better understand the various circulating drug forms by allowing for variant quantitation.Results: An immunocapture LC–MS method for quantitation of a biotherapeutic monoclonal antibody from human plasma is presented. Sensitivity, precision and accuracy for each molecular portion are presented along with an example of glycoform variant quantitation.Conclusion: The method is presented as a basic platform to be further developed for Good Practice (GxP) applications, critical quality attribute analysis or general understanding of molecular forms present as required for the wide range of drug development processes.